2022
DOI: 10.1002/trc2.12239
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of fasting glucose and longitudinal Alzheimer's disease imaging markers

Abstract: Introduction: Fasting glucose increases with age and is linked to modifiable Alzheimer's disease risk factors such as cardiovascular disease and Type 2 diabetes (T2D). Methods:We leveraged available biospecimens and neuroimaging measures collected during the Alzheimer's Prevention Through Exercise (APEx) trial (n = 105) to examine the longitudinal relationship between change in blood glucose metabolism and change in regional cerebral amyloid deposition and gray and white matter (WM) neurodegeneration in older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
0
11
1
Order By: Relevance
“…Elevated glucose, insulin resistance, and type 2 diabetes induce chronic inflammation and oxidative stress and are increasingly linked to elevated risk for AD ( Khan and Hegde, 2020 ). Human studies suggest that consuming a high glycemic diet ( Taylor et al, 2017 , 2021 ) and worsening glucoregulation ( Morris et al, 2016 ; Gomez et al, 2018 ; Honea et al, 2022 ) are related to increased Aβ burden in cognitively normal older adults, even in those without diabetes. Individuals with diabetes that have higher peripheral fasting glucose levels also have higher brain glucose levels, which is suggested to alter brain Aβ processing and clearance ( Heikkila et al, 2009 ; Madhusudhanan et al, 2020 ).…”
Section: Ketotherapies and Amyloid-βmentioning
confidence: 99%
“…Elevated glucose, insulin resistance, and type 2 diabetes induce chronic inflammation and oxidative stress and are increasingly linked to elevated risk for AD ( Khan and Hegde, 2020 ). Human studies suggest that consuming a high glycemic diet ( Taylor et al, 2017 , 2021 ) and worsening glucoregulation ( Morris et al, 2016 ; Gomez et al, 2018 ; Honea et al, 2022 ) are related to increased Aβ burden in cognitively normal older adults, even in those without diabetes. Individuals with diabetes that have higher peripheral fasting glucose levels also have higher brain glucose levels, which is suggested to alter brain Aβ processing and clearance ( Heikkila et al, 2009 ; Madhusudhanan et al, 2020 ).…”
Section: Ketotherapies and Amyloid-βmentioning
confidence: 99%
“…Meanwhile, our MVMR results revealed that the causal effect of OCN on AD was also partially dependent of glucose metabolism, especially for FG. Numerous studies have showed that impaired FG was related to increased cerebral beta-amyloid accumulation and atrophy, and associated with a higher risk of AD [ 67 , 68 ]. It is reported that the levels of glucose transporter-3 in AD patients were decreased, leading to impaired glycolytic flux, which was related to the severity of AD pathology [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The DTI data were analyzed using FSL 6.1 software. Data processing steps included eddy current & motion correction applying the FDT tool, brain extraction applying the BET tool, and DTI measure reconstruction applying the DTI-FIT tool ( Honea et al, 2022 ). Additionally, to evaluate the microstructural changes in white matter, the fractional anisotropy (FA) and mean diffusivity (MD) values based on WMH and NAWM mask were extracted employing Matlab code, which are widely used to evaluate the microstructural integrity of white matter fibers.…”
Section: Methodsmentioning
confidence: 99%